High prevalence of Foxp3 and IL17 in MMR-proficient colorectal carcinomas. Issue 6 (26th October 2007) - Le Gouvello, S; Bastuji-Garin, S; Aloulou, N; Mansour, H; Chaumette, M-T; Berrehar, F; Seikour, A; Charachon, A; Karoui, M; Leroy, K; Farcet, J-P; Sobhani, I
Abstract : Background and aims: Colorectal cancer (CRC) harbours different types of DNA alterations, including microsatellite instability (MSI). Cancers with high levels of MSI (MSI-H) are considered to have a good prognosis, probably related to lymphocyte infiltration within tumours. The aim of the present study was to characterise the intratumoural expression of markers associated with the antitumour immune response in mismatch repair (MMR)-proficient (MSS) colon cancers. Methods: Ninety human colon cancers (T) and autologous normal colon mucosa (NT) were quantified for the expression of 15 markers of the immune response with quantitiative reverse transcription-PCR (qRT-PCR). mRNA expression levels were correlated with MMR status. Immunohistochemistry (IHC) was performed using both interleukin 17 (IL17) and CD3 antibodies. Results: Expression of cytotoxic markers (FasL, granzyme B and perforin), inflammatory cytokines (IL1β, IL6, IL8, IL17 and transforming growth factor β (TGFβ)) and a marker of regulatory T cells (forkhead box P3 (Foxp3)) was significantly higher in tumours than in autologous normal tissues. Adjusting for MMR status, higher tumoural expression of both granzyme B and perforin was associated with the MSI-H phenotype, and the perforin T/NT ratio was higher in MSI-H tissues than in MSS tissues. Higher tumoural expression of Foxp3, IL17, IL1β, IL6 and TGFβ was associated with the MSS phenotype, and the IL17 T/NT ratio was higher in MSS tissues than in MSI-H tissues as assessed by both qRT-PCR and IHC. Conclusions: Immune gene expression profiling in CRC displayed different patterns according to MMR status. Higher Foxp3, IL6, TGFβ and IL17 expression is a particular determinant in MMR-proficient CRC. These may be potential biomarkers for a new prognostic "test set" in sporadic CRCs.